2014
DOI: 10.12816/0023979
|View full text |Cite
|
Sign up to set email alerts
|

Extrinsic Stain Removal with a Toothpowder : A Randomized Controlled Trial

Abstract: Abstract:Objectives: The efficacy of a commercially available toothpowder was compared with toothpaste in removing extrinsic dental stains. Methods:In this single-blind, randomized controlled trial, 77 volunteers were included from a residential professional college. All study subjects (control toothpaste users and test toothpowder users) plaque control measures. All study subjects were instructed to rinse with 5 ml 0.12% chlorhexidine mouthwash for 1 minute, twice and one cup of double tea bag solution three … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 13 publications
(9 reference statements)
0
10
0
Order By: Relevance
“…In spite of numerous techniques and materials being available for getting rid of the plaque and extrinsic stains, none has qualified as a gold standard treatment modality till date. Routine home dental polishing done with powered toothbrush[ 5 6 ] and whitening paste,[ 7 8 ] although effective, still lacks efficiency in inaccessible areas, thus necessitating a more efficient professional polishing other than conventional rubber-cup polishing.…”
Section: Introductionmentioning
confidence: 99%
“…In spite of numerous techniques and materials being available for getting rid of the plaque and extrinsic stains, none has qualified as a gold standard treatment modality till date. Routine home dental polishing done with powered toothbrush[ 5 6 ] and whitening paste,[ 7 8 ] although effective, still lacks efficiency in inaccessible areas, thus necessitating a more efficient professional polishing other than conventional rubber-cup polishing.…”
Section: Introductionmentioning
confidence: 99%
“…On the market of dental materials intended for use in the dental office there are many pastes for professionally cleaning teeth of extrinsic stains. An important function of a dentifrice is the control of extrinsic tooth discoloration caused by certain dietary components, tobacco, or drugs that are associated with protein compounds found in enamel structure and surface [6,17]. α = 0.05) (Figure 3).…”
Section: Discussionmentioning
confidence: 99%
“…The appearance of discolouration on the surface of tooth tissues is often associated with the use by patients of certain stimulants (mainly tobacco), medicines (chlorhexidine or tin salts), and the consumption of staining drinks (coffee, tea). The source of dyes may also be metabolites of oral bacteria (Neisseria, Porphyromonas, Actinomyces) [1,3,6,8,11,16].…”
Section: O R I G I N a L Pa P E Rmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to extrinsic coloring agents, several studies have described that due to the brushing process, the teeth can indirectly develop a composite resin surface roughness, which can trigger color changes. However, other studies have reported that a tooth brushing process can actually help removing extrinsic stains, which physically bind to the surface of the teeth as well as aid in composite resin restorations [10].…”
Section: Introductionmentioning
confidence: 99%